Parenting Styles, Loneliness and Problematic Internet Use Among Adolescents: A Cross-Sectional Analysis - Zulkarnain, Zulkarnain; Tarmidi, Tarmidi; Purwasih, Eni; Bochaver , Sofya Nartova (Journal of Education Culture and Society, 2025)
Aim. The aim of this study is to explore the relationships between parenting styles, loneliness, and problematic internet use among adolescents, and to determine the contributions of these factors to PIU.Methods. The study involved 529 high school students aged 15 to 18 years. Data was collected using structured questionnaires and analysed through stepwise regression to assess the impact of different parenting styles and loneliness on PIU.Results. The study found that authoritative parenting emerged as a strong negative predictor of problematic internet use (PIU). Adolescents who experienced authoritative parenting, a style marked by high levels of both responsiveness and demand—tended to have lower levels of PIU. Conversely, authoritarian, permissive, and loneliness were identified as positive predictors of PIU.Conclusions. These findings emphasise the importance of both parenting style and emotional well-being in influencing adolescents' internet use behaviour. Effective interventions should address these factors to help reduce PIU and promote healthier online habits. Authoritative parenting plays a significant role in reducing PIU among adolescents. Interventions that promote authoritative parenting practices and address loneliness are recommended as effective strategies for mitigating PIU.